(untitled) (The New Uzbekistan Journal of Medicine, 2025)
Artificial Intelligence (AI) technologies have become a crucial factor in the development of clinical decision support systems in healthcare. These systems assist physicians in patient diagnosis, treatment planning, and health monitoring, making the decision-making process more efficient and accurate. The article analyzes the principles, architecture, and main functions of AI-based clinical decision support systems. Additionally, it discusses the advantages of their application in medicine, particularly their role in disease detection and prevention, as well as existing limitations and ethical issues. Through examples of modern systems, the effectiveness of AI and its future prospects are examined. This article is useful for medical professionals, IT specialists, and researchers, promoting the wider adoption of digital technologies in clinical practice.